SIFAT PAPAN WOL KAYU DARI 17 JENIS KAYU IRIAN JAYA - I M Sulastiningsih; Rozak Memed; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
The result of laboratory tests on the properties of wood-woo/boards made from 17 wood species obtained from lrian Jaya are reported in this paper. The test comprised board density, moisture content, thickness reduction due to compression and bending strength.The study reveals that the average yield of wood-wool is 312 kg per cubic meter of log input. The physical and mechanical properties of wood-wool boards from five wood species mineralized with CaCl2 solution or Ca(OH)2 suspension are in compliance with the DIN 1101 standard.